Пути создания пароплазменных установок для газификации низкосортных углей и отходов углеобогащения - Давыдов, С.Л. (Геотехническая механика, 2009)
Проведено аналіз існуючих схем газифікації твердого палива. Наведені переваги та недоліки різних методів газифікації. Надано обґрунтування для подальшої розробки реактора з пароплазмової газифікації низькосортного вугілля та відходів вуглезбагачення. The analysis of the extant gasification schemes of solid fuel is realized. The advantages and shortages of different methods of gasification are resulted. The substantiation for post development of reactor with steam plasma gasification of the low-grade coal and waste coal is given.